Rural resilience in the era of climate change: Community-based natural resource governance in coastal communities - Simon Sumanjoyo Hutagalung; Dedy Hermawan (Interaction, Community Engagement, and Social Environment, 2026)
Background: Climate change is increasingly threatening the sustainability of rural communities whose livelihoods depend on natural resources. Although previous studies have emphasized the importance of community participation, local ecological knowledge, and collective governance in climate adaptation, limited empirical evidence explains how multiple community-based natural resource management (CBNRM) practices interact to strengthen village resilience within a social–ecological system. This study examines the role of CBNRM in enhancing climate resilience in villages of Rajabasa District, South Lampung Regency, Indonesia. Methods: A qualitative case study involving 24 purposively selected informants from two villages was conducted, complemented by observations and document analysis. Data were analyzed through thematic analysis focusing on four dimensions: community-based water management, adaptive agricultural practices, land conservation, and human–environment relationships. Data saturation was reached across informant groups. Findings: Community-based water governance, adaptive farming based on local ecological knowledge, collective land conservation, and strong social institutions are interconnected adaptive mechanisms that enhance village resilience. Water distribution is coordinated through farmer groups, agricultural adaptation is guided by local ecological knowledge and crop diversification, and soil productivity and water recharge areas are protected by conservation practices norms, cooperation, and local institutions strengthen adaptive capacity under increasing climate uncertainty. Conclusion: By integrating ecological knowledge, collective action, and sustainable environmental governance into mutually reinforcing adaptation strategies, community-based natural resource management enhances village resilience. Novelty/Originality of this article: This study extends the CBNRM, Social-Ecological Systems, and Adaptive Governance literature by demonstrating that village resilience emerges through the interaction of local institutions, ecological knowledge, and collective governance.